2018
DOI: 10.15406/icpjl.2018.06.00175
|View full text |Cite
|
Sign up to set email alerts
|

Role of immunohistochemical markers in breast cancer and their correlation with grade of tumour, our experience

Abstract: Objectives: To study the immunohistochemical markers in invasive carcinoma of breast and to assess the relationship of hormonal receptors and Her2Neu oncoprotein with grade of tumour. Materials and methods: This was a comparative cross sectional study conducted at Chughtais Lahore lab from Jan 2011-Oct 2011. Eighty two biopsy proven cases of breast carcinoma were reviewed. Immunohistochemistry was used to evaluate the expression of Estrogen receptors(ER) and progesterone receptors (PR) and Her2Neu oncoprotein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Regarding the heterogeneity of breast cancer [17,18], the latest classifications established by the World Health Organization take into account the variability of the morphological, phenotypic and molecular profile of this type of cancer [6,9]. The state of hormone receptors has become a predictor of response to hormonal therapy with tamoxifen in women with hormone-dependent breast cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the heterogeneity of breast cancer [17,18], the latest classifications established by the World Health Organization take into account the variability of the morphological, phenotypic and molecular profile of this type of cancer [6,9]. The state of hormone receptors has become a predictor of response to hormonal therapy with tamoxifen in women with hormone-dependent breast cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…The previous research used a 5 mg dose of DMBA induction and 65 mg/kg BW single dose which showed that the most frequent image was grade 1, then grade 2, and the fewest was grade 3 [37], [39]. In general, in human breast cancer, the most frequent is grade 2 [40], [41]. Histopathological grading showed cell differentiation level and it had a relation with a bad prognosis of human breast cancer [42].…”
Section: Histopathological Type Of Dmba-induced Mammary Cancermentioning
confidence: 99%
“…PR expression is strongly dependent on ER expression. Tumors expressing PR but not expressing ER are very rare (<1% of breast carcinoma cases) (16). ER negative breast carcinomas increasingly do not resemble the cell of origin and tend to have more severe genetic mutations, such as p53, HER2, BRCA1 mutations and higher genomic instability (2,3).…”
Section: Grade Relationship With Er and Pr Expressionmentioning
confidence: 99%